Building MSMEs Resilience with the Role of Digitalization and Human Resource Practices - Kamalin, Salu Faza; Sari, Siti Ayu Nita; Suzana, Anna (Research Collaboration Community (RCC), 2025)
This study highlights the important role of digitalization and human resource management in strengthening the resilience of MSMEs in Cirebon City. Using a quantitative approach based on SEM-PLS, this study analyzed 173 MSMEs in the culinary sector. The results show that digitalization has a positive impact on the resilience of MSMEs, although the effect is not as great as the role of human resource management. The R-square value of 0.652 indicates that these two factors together explain 65.2% of the variation in MSME resilience. Therefore, this study recommends strengthening digitalization strategies and improving the quality of human resource management through training and supportive policies, in order to improve the competitiveness and sustainability of MSMEs in the face of economic and social dynamics in the digital era.